The lost boy : a foster child's search for the love of a family - Pelzer, David J. (Deerfield Beach, Fla. : Health Communications, 1997)
Describes the life of a small boy who is brutally abused in his biological home by his alcoholic mother and receives no support from his helpless father. He is placed in a succession of five foster homes constantly searching for a family that will love him.
5.1.
9-Adult.
720
Accelerated Reader AR-ATOS
Reading Counts RC
Keywords: Pelzer, David J; Abused children -- California -- Daly City -- Biography; Children of alcoholics -- California -- Daly City -- Biography; Abusive mothers -- Family relationships -- California -- Daly City; Family violence -- California -- Daly City; Foster home care -- California -- Case studies